Pengaruh Pemahaman Materi Akhlak Berpakaian Terhadap Etika Berbusana Muslimah Pada Siswi Kelas XII Di MAN 1 Kota Bogor - Liyana, Salsabila; Gustiawati, Syarifah; Yono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to: (1) To Know and explain the level of understanding of class XII female students regarding the material on dress morals at MAN 1 Bogor City, (2) To Know and explain the level of application of Muslim dress ethics for class XII female students at MAN 1 Bogor City, (3) To know and explain the influence of understanding the material on morals of dress on the dress ethics of Muslim female in class XII at MAN 1 Bogor CityThis research uses quantitative methods with the data analysis technique used, namely simple linear regression with t-test. The number of samples in this study was 51 respondents with sample determination using random sampling techniques. The data collection technique is by distributing questionnaires. Based on the data obtained, it shows that the level of understanding of class XII female students' clothing morals is in the very high category with an average value of 69.37 and the level of clothing ethics of class XII female Muslim students is included in the high category with an average value of 62.09. The results of the research show that understanding the material on morals in clothing has a positive effect on the ethical clothing of Muslim female in class XII at MAN 1 Bogor City. This can be seen from the results of a simple analysis where the equation Y = 11.806 + 0.725X is obtained. The t-test results showed that tcount was 5,947 > ttable 1,677 with a significance of 0.000 < 0.05. So, Ha is accepted and Ho is rejected. The influence of understanding clothing morals on Muslim females clothing ethics is 41.9%, while the remaining 58.1% is explained by other variables that were not studied.